2003
DOI: 10.1046/j.1095-8649.2003.00151.x
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of rodlet cells in chub caused by the herbicide Stam® M‐4 (Propanil)

Abstract: Handling stress and exposure to the herbicide Stam® M‐4 (Propanil) were associated with an exponential depletion of the rodlet cells (RC) in the bulbus arteriosus of chub Leuciscus cephalus. Structural changes of the RC in herbicide‐exposed fish were encountered, including the occurrence of myeloid bodies in the cytoplasm of the RC of the intestine, various degrees of rodlet degeneration and high vacuolization in the cytoplasm of RC in almost all examined organs of exposed chub.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 19 publications
1
52
0
1
Order By: Relevance
“…Proteolytic activity of RCs was described by others [20,21]. Recently Dezfuli et al [22] reported a close association between RCs and eosinophilic granule cells (EGCs) and Reite [23] suggested that these cells may exert independent functions in the inflammatory network of fish. Administration of synthetic corticosteroids affects the expression of surface adhesion molecules of RCs [1] as in leucocytes [24e26].…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Proteolytic activity of RCs was described by others [20,21]. Recently Dezfuli et al [22] reported a close association between RCs and eosinophilic granule cells (EGCs) and Reite [23] suggested that these cells may exert independent functions in the inflammatory network of fish. Administration of synthetic corticosteroids affects the expression of surface adhesion molecules of RCs [1] as in leucocytes [24e26].…”
Section: Introductionmentioning
confidence: 89%
“…This suggests a function in stress physiology and thus RC numbers may be useful as biomarkers for stressors and chemical agents [9,22].…”
Section: Introductionmentioning
confidence: 97%
“…Within the last decade, many authors favoured the hypothesis that they represent inflammatory cells, thus belonging to the host defence system [2,7]. Increased counts of RCs and/or EGCs after parasites infection [3e5,8e13], and exposure to diverse chemicals and environmental stressors [7,14,15] supported that hypothesis. On the other hand, a few studies suggested that the frequency of both EGCs and RCs in a particular tissue or organ can vary independently of the presence of parasites or of the water quality and can vary due to some endogenous factors [16e19].…”
Section: Introductionmentioning
confidence: 95%
“…A change in the number of rodlet cells has been described under parasitic infection (Leino 1996;Reite 1997;Giari et al 2006;Dezfuli et al 2007b, c, d, e), variation of salinity ) and season (Leino 2001) and mechanical and chemical damages (Manera and Dezfuli 2004). Dezfuli et al (2003Dezfuli et al ( , 2006 demonstrated an increase in number of rodlet cells in gills of Leuciscus cephalus and in several tissues (gills, intestine and kidney) of D. labrax after exposure to herbicides. Courtney and Couch (1988) suggested a correlation between rodlet cells and carcinogenic insult in Cyprinodon variegatus exposed to the carcinogen n-nitrosodiethylamine.…”
Section: Discussionmentioning
confidence: 93%
“…The aim was to investigate if overcrowding affects the number of rodlet cells in gills since these cells might be candidate quantitative and qualitative biomarkers for stressors and chemical agents (Dezfuli et al 2003). Repeated or prolonged exposure of fish to common stressors such as handling and net confinement activates the hypothalamic- pituitary-interrenal axis leading to increased plasma cortisol, decreased growth rates and an increased incidence of disease (Wendelaar Bonga 1997; Mommsen et al 1999).…”
Section: Discussionmentioning
confidence: 99%